Photoelectrochemical concurrent hydrogen generation and heavy metal recovery from polluted acidic mine water - Ian Mabbett (Sustainable Energy & Fuels, 2021)
The feasibility of a solar-driven photoelectrochemical process to generate hydrogen fuel from metal mine polluted water while simultaneously recovering heavy metals has been explored. Electron transport from the photoanode to the cathode plays a key role in generating hydrogen (37.6 µmol h–1 cm–2 at 0.2 V RHE, 1 sun illumination), and scavenging Zn2+ ions in the form of ZnO.